Research Progress on the Relationship between Mental Health and Sleep Disorders - sun lei (Pacific International Journal, 2023)
The relationship between mental status and sleep disorders has gained significant attention in recent years. Extensive research has elucidated a bidirectional association between these two domains, highlighting the impact of mental health on sleep and the influence of sleep disturbances on mental well-being. This review provides an overview of the current progress in understanding this complex relationship.In exploring the impact of mental health on sleep disorders, the effects of anxiety, stress, depression, and bipolar disorder on sleep quality and patterns are discussed. Conversely, the influence of sleep disorders, such as insomnia, sleep apnea, and narcolepsy, on mental health outcomes is examined. Neurobiological mechanisms, including shared neural pathways and neurotransmitter dysregulation, as well as the disruption of circadian rhythms, are explored as underlying factors linking mental health and sleep disorders.Moreover, the review discusses various treatment approaches and interventions for individuals with comorbid mental health and sleep disorders. Psychological interventions, pharmacological options, and lifestyle modifications are highlighted as strategies to improve both mental health and sleep outcomes.The review concludes by identifying research gaps, calling for continued interdisciplinary collaboration, and emphasizing the importance of public awareness and education. Future directions and implications for addressing this intricate relationship are discussed to enhance our understanding and develop effective interventions.Overall, the review underscores the significance of recognizing and addressing the bidirectional relationship between mental status and sleep disorders, with the ultimate goal of improving the well-being of individuals affected by these conditions.